Analysis of Health Literacy with Dental Caries and Stunting in Toddlers in Jambi City in 2023 - Nurmawi, Yesi; Mahsalisa, Febrita (Riset Informasi Kesehatan; Vol 13 No 1 (2024): Riset Informasi KesehatanDO - 10.30644/rik.v13i1.828, 2024)
Background : Dental caries causes children to experience loss of chewing power (impaired chewing function), affects appetite, nutritional intake and disruption of digestion and results in less than optimal growth, which ultimately will affect the child's nutritional status. A person's health status can be maintained and improved with health literacy. Method : The purpose of the study was to to analyze health literacy with dental caries and stunting in toddlers. Results : Research found that dental caries was 55% and the incidence of stunting was 17.5% in toddlers, as well as 40.0% low literacy. There is a relationship between health literacy and dental caries status and the incidence of stunting in toddlers. Conclusion : The role of maternal parenting based on high and adequate health literacy can prevent and control dental caries status and the incidence of stunting in toddlers.